Retinopathy of Prematurity (ROP): An Overview of Biomarkers in Various Samples for Prediction, Diagnosis, and Prognosis - Huang D; Liu Z; Deng Y (Clinical Ophthalmology)
Dan Huang,1 ZhuoQi Liu,2 Yan Deng1,3 1Department of Ophthalmology Center, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, People’s Republic of China; 2Department of Biochemistry and Molecular Biology, School of Basic Medical Sciences, Jiangxi Medical College, Nanchang University, Nanchang, People’s Republic of China; 3Jiangxi Key Laboratory of Molecular Medicine, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, People’s Republic of ChinaCorrespondence: ZhuoQi Liu, Department of Biochemistry and Molecular Biology, School of Basic Medical Sciences, Jiangxi Medical College, Nanchang University, Nanchang, People’s Republic of China, Tel +18970949577, Email liuzhuoqi@ncu.edu.cn Yan Deng, Department of Ophthalmology Center, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, People’s Republic of China, Tel +15970464160, Email dengyan789789@hotmail.comAbstract: Retinopathy of Prematurity (ROP) is a proliferative retinal vascular disease marked by abnormal development of retinal vessels in low birth weight preterm infants. It is one of the leading causes of blindness in preterm infants. Current ROP screening methods impose high demands on both the equipment and the expertise of ophthalmologists, which limits their widespread application, particularly in secondary hospitals and remote areas. Thus, the identification of relevant biomarkers and the development of simpler detection methods are important and promising. Non-invasive or minimally invasive sampling methods, along with biomarkers possessing high sensitivity and specificity, could greatly enhance neonatal screening, facilitate early diagnosis, and improve prevention of blindness in preterm infants. This review provides relevant medical insights for clinical practice. This review explored, compares and analyzes various sampling sources. It compares and analyzes research on ROP-related biomarkers derived from these samples.Plain Language Summary: This review compares different human fluid sampling sources for screening, predicting, diagnosing, and prognosticating ROP patients, and compares and analyzes the research on ROP-related biomarkers from different samples. Non-invasive or minimally invasive methods of obtaining samples and selecting biomarkers with high validity promise to be more beneficial for newborn, early diagnosis of ROP, and better prevention of blindness in preterm infants, providing relevant medical references for clinical practice.Keywords: retinopathy of prematurity, biomarkers, neonatal screening, early diagnosis